ANALISIS USAHA, NILAI TAMBAH DAN KESEMPATAN KERJA AGROINDUSTRI TEMPE DI KOTA BANDAR LAMPUNG - Vidya Putri Kemala; Agus Hudoyo; Achdiansyah Soelaiman (Lampung University, 2019)
The objectives of this study are to analyze the business, the added-value, and employment of the tempeh agroindustry in Bandar Lampung. This study is in conducted in three production centers, i.e. Gunung Sulah, Sawah Brebes, and Kedamaian. Respondents were 60 randomly chosen tempeh home industry owners. The data were analyzed using financial analysis and the added-value analysis. The average net revenue over its cash cost was Rp9.45 million/month. The average net revenue over its total cost was Rp5.62 million/month. The average standard cost was Rp8,452/kg tempeh. The average added-value was Rp4,117/kg soybeans and its 95 percent confidence interval was Rp3,001-5,233/kg soybeans. In the three tempeh production centers, the number of people employed was 186.Key words : agroindustry tempeh, added value,business analysis, employment.